Hybrid Heterostructure Ni3N|NiFeP/FF Self‐Supporting Electrode for High‐Current‐Density Alkaline Water Electrolysis. Issue 4 (28th February 2023) - Li, Jingwen; Song, Min; Hu, Yezhou; Zhu, Ye; Zhang, Jian; Wang, Deli
Abstract: Exploring earth‐abundant and efficient electrocatalysts for oxygen evolution reaction (OER) is an urgent need and significant to water electrolysis. Although great achievements have been made, it is still challenging to achieve industrial current density and stability. Herein, a hybrid heterostructure electrode based on Ni3 N and NiFeP over Fe foam substrate (Ni3 N|NiFeP/FF) is reported, along with 3D‐interconnected hierarchical porous architecture, achieving the low overpotentials of 287, 178, and 290 mV at 500 mA cm −2 in 1 m KOH, 30 wt% KOH, and alkaline simulated seawater, respectively, with excellent durability at 800 mA cm −2 over 120 h, which can satisfy the requirements of industrial water electrolysis. Here, the hybrid heterostructure can ensure the low energy barrier of the catalytic active sites, the 3D‐interconnected hierarchical porous architecture can facilitate the fast mass/ions/electrons transformation, which contributes together to boost the superb water splitting performance. Furthermore, the COMSOL simulations confirm the multiple merits of the designed electrode during the water electrocatalysis. The present work provides a new strategy in the design and engineering of high‐performance electrodes for industrial water electrolysis. Abstract : A self‐supported 3D‐interconnected hierarchical porous electrode with abundant hybrid heterostructure is designed and constructed, and achieving superb overall water‐splitting performance in both alkaline‐ and alkaline‐simulated seawater conditions at industrial current density.